Study of the role of the acceptor stem in the interactions between tRNAs and aminoacyl-tRNA synthetases. - Bonnet, J (1975)
Several studies have clearly demonstrated that the end of the acceptor stem was a very important area determining the aminoacylation properties of tRNAs. However the attempts to measure the contribution of this region to the binding of tRNAs to aminoacyl-tRNA synthetases have led to contradictory results. We report here the stepwise degradation of yeast tRNA-Phe and tRNA-Val from their 3' terminus, up to the seventh nucleotide : the affinity of each of the degraded-tRNA for their cognate aminoacyl-tRNA synthetase was compared to that of intact tRNA and it was found that these affinities are not significantly decreased when compared to those of the intact tRNAs.